The SIBELIUS Project: E Pluribus Unum. Issue 1 (12th November 2021) - Sawala, Till; McAlpine, Stuart; Jasche, Jens; Lavaux, Guilhem; Jenkins, Adrian; Johansson, Peter H; Frenk, Carlos S
ABSTRACT: We introduce 'Simulations Beyond The Local Universe' (SIBELIUS) that connect the Local Group (LG) to its cosmic environment. We show that introducing hierarchical small-scale perturbations to a density field constrained on large scales by observations provides an efficient way to explore the sample space of LG analogues. From more than 60 000 simulations, we identify a hierarchy of LG characteristics emanating from different scales: the total mass, orientation, orbital energy, and the angular momentum are largely determined by modes above λ = 1.6 comoving Mpc (cMpc) in the primordial density field. Smaller scale variations are mostly manifest as perturbations to the MW–M31 orbit, and we find that the observables commonly used to describe the LG – the MW–M31 separation and radial velocity – are transient and depend on specifying scales down to 0.2 cMpc in the primordial density field. We further find that the presence of M33/LMC analogues significantly affects the MW–M31 orbit and its sensitivity to small-scale perturbations. We construct initial conditions that lead to the formation of an LG whose primary observables precisely match the current observations.